1998
DOI: 10.1074/jbc.273.40.25537
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids Decrease Expression of Promoters with Sterol Regulatory Elements by Decreasing Levels of Mature Sterol Regulatory Element-binding Protein

Abstract: Membrane physiology, plasma lipid levels, and intracellular sterol homeostasis are regulated by both fatty acids and cholesterol. Sterols regulate gene expression of key enzymes of cholesterol and fatty acid metabolism through proteolysis of the sterol regulatory elementbinding protein (SREBP), which binds to sterol regulatory elements (SRE) contained in promoters of these genes. We investigated the effect of fatty acids on SREdependent gene expression and SREBP. Consistent results were obtained in three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
4
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(229 citation statements)
references
References 32 publications
8
213
4
4
Order By: Relevance
“…Cell culture studies have clearly shown that PUFA have the ability to reduce SREBP1a and 1c mRNA and SREBP1 protein concentrations (Worgall et al, 1998). In our own experiments in the hamster feeding PUFA reduces mRNA for all three SREBPs in a manner that is dependent on the nature of the PUFA (Figure 3a).…”
Section: Regulation Of Gene Expression By Dietary Lipidsmentioning
confidence: 57%
“…Cell culture studies have clearly shown that PUFA have the ability to reduce SREBP1a and 1c mRNA and SREBP1 protein concentrations (Worgall et al, 1998). In our own experiments in the hamster feeding PUFA reduces mRNA for all three SREBPs in a manner that is dependent on the nature of the PUFA (Figure 3a).…”
Section: Regulation Of Gene Expression By Dietary Lipidsmentioning
confidence: 57%
“…In 293 and other cultured mammalian cells, proteolysis of SREBP-1a and SREBP-2 has been shown to be induced by cholesterol withdrawal (21,29,30). Moreover, growth in medium lacking unsaturated fatty acids promotes the activation of SREBP-1a and SREBP-1c͞ADD1 (24,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which oleate mediates or induces SREBP-1c and lipogenic gene expression remains to be explored. Several in vitro studies have shown that oleate suppresses the proteolytic processing of SREBP-1 protein and reduces SREBP-1 and lipogenic gene expression (52)(53)(54). The inhibitory effect has been proposed to be attributed to the increase in the release of ceramide from sphingomyelin (55).…”
Section: Discussionmentioning
confidence: 99%